Implementasi Mediasi Elektronik di Pengadilan Agama Medan Tinjauan PERMA No. 3 Tahun 2022 tentang Mediasi Elektronik - Riyaldi, M.; Akbar, Ali (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Electronic mediation has been implemented by several courts, including the Medan Religious Court. This study addresses the following research questions: How is electronic mediation implemented in the Medan Religious Court based on Supreme Court Regulation (PERMA) No. 3 of 2022? What are the challenges encountered in its implementation? This research employs a qualitative method with an empirical approach. Data collection techniques include observation, interviews, and documentation. The findings indicate that the implementation of electronic mediation in the Medan Religious Court aligns with PERMA No. 3 of 2022. The court has designated personnel responsible for managing the equipment used in electronic mediation. The available facilities, including mediation rooms, laptops, projectors, and the Zoom application, are sufficient to conduct electronic mediation. However, several challenges hinder the process, including network disruptions that reduce mediation effectiveness, limited proficiency of involved parties in using online mediation applications, reduced direct interaction between mediators and disputing parties, and concerns regarding mediation confidentiality due to potential third-party interventions.